Perencanaan Biaya, Jadwal Proyek Dermaga dan Bangunan Pelengkap Sebagai Kebutuhan Infrastruktur Penunjang Pariwisata - Puah, Putri Sri; Meilawaty, Okta; Novi, Novi; Rahmania, Najwamuna Norazizah; Friskila, Ayunisha; Ginting, Messy May Tania BR; Sopariah, Iis (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
The construction of a pier in Desa Pulau Telo Baru, Kapuas Regency, aims to enhance the local economy and support the development of sustainable tourism. This project involves community participation in natural resource management and environmental preservation, as well as the development of a food court as a social area for visitors and locals. The methods used in this research include village potential discussions, field surveys, and the collection of primary data related to geographical and socio-economic conditions. The research results are in the form of a Budget Plan (RAB) covering preparatory work, reclamation, substructure, and foundation, with a total budget of IDR 1,484,659,068.00. The construction of the pier and food court improves transportation accessibility, attracts more tourists, and contributes to tourism sustainability and the improvement of the local community's quality of life. This project creates job opportunities, increases the community's income, and strengthens infrastructure to support tourism activities.